Qualitative Assessment of Bacteria and Fungi in the Indoor Environment of Hospitals of Islamabad, Pakistan: Bacteria and Fungi in Hospital Indoor Air - Hussain, Fouzia; Tahir, Subhe Sadiq; Rauf, Naseem; Batool, Afifa (Biological Sciences - PJSIR, 2012)